2012
DOI: 10.1186/2049-1891-3-17
|View full text |Cite
|
Sign up to set email alerts
|

Poultry fat decreased fatty acid transporter protein mRNA expression and affected fatty acid composition in chickens

Abstract: BackgroundA study was undertaken to examine the effects of poultry fat (PF) compared with those of soybean oil (SBO) on intestinal development, fatty acid transporter protein (FATP) mRNA expression, and fatty acid composition in broiler chickens. A total of 144 day-old male commercial broilers were randomly allocated to 2 treatment groups (6 replicates of 12 chicks for each treatment) and fed isocaloric diets containing 3.0% PF or 2.7% SBO at 0 to 3 wk and 3.8% PF or 3.5% SBO at 4 to 6 wk, respectively.Results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…The response of fabp expression to dietary lipid level may also be related to the fatty acid profile of the diets. In general, different fabp isoforms reveal distinct binding preferences for specific fatty acids [35,49]. In this study, the higher lipid level was obtained by adding fish oil into the control diet, resulting in high LC-PUFA levels in high-lipid diets.…”
Section: The Liver Fabp Expression In Response To Dietary Lipidmentioning
confidence: 91%
“…The response of fabp expression to dietary lipid level may also be related to the fatty acid profile of the diets. In general, different fabp isoforms reveal distinct binding preferences for specific fatty acids [35,49]. In this study, the higher lipid level was obtained by adding fish oil into the control diet, resulting in high LC-PUFA levels in high-lipid diets.…”
Section: The Liver Fabp Expression In Response To Dietary Lipidmentioning
confidence: 91%
“…Enterocytes also express an active sodium-glucose symporter (SGLT1) on the apical membrane that utilizes the concentration gradient of Na + to transfer glucose against its concentration [ 15 ]. Absorption of lipids and fatty acids occur through fatty acid-binding proteins (FABPs) and fatty acid transport proteins (FATPs) that are expressed on the apical membrane of the intestinal mucosal cells [ 16 , 17 ]. The di- and tripeptides are absorbed via H + -dependent peptide transporters (PEPT1 and PEPT2), and peptide/histidine transporter 1 (PHT1) [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, direct feeding of ALA did not significantly affect FABP1 in the liver of laying hens ( Neijat et al, 2017 ). However, some studies have found that high levels of dietary fat can increase the expression of FATP and FABP mRNA in the liver ( Yuan et al, 2012 ), as well as the expression of FABP in the intestine ( Katongole and March, 1980 ). In our experiment, feeding flaxseed oil resulted in high expression of FABP1 and FATP1 in liver and duodenum.…”
Section: Discussionmentioning
confidence: 99%